2019
DOI: 10.21873/invivo.11707
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic Vein Cut-down for Totally Implantable Central Venous Access Devices With Preoperative Ultrasonography by Surgical Residents

Abstract: Background/Aim: Cephalic vein (CV) cut-down for totally implantable central venous access devices (TICVADs) is not frequently used due to its low success rate. We compared the outcomes of CV cut-down using preoperative ultrasonography (US) performed by experienced surgeons versus surgical residents. Patients and Methods: From December 2015 to December 2017, 10 surgeons implanted 212 TICVADs using CV cut-down with preoperative US. The surgeons were divided into two groups of five each: surgical residents (Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Studying laterality, in most studies the rate is higher via RCV, both without (95.5%) 15 and with POUS (95.8%). 16 In this study the success rate via LCV was higher than that found via RCV, 98.5%, although not significantly.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Studying laterality, in most studies the rate is higher via RCV, both without (95.5%) 15 and with POUS (95.8%). 16 In this study the success rate via LCV was higher than that found via RCV, 98.5%, although not significantly.…”
Section: Discussioncontrasting
confidence: 53%
“…We have had 5.0% postoperative/delayed complications, while those observed in other studies range between 1.3% 18 and 15.7%. 17 System infection is the most concerning complication of the TIVAPs, as it usually requires explantation, and the figures range between 1.6% 16 and 10.8%. 19 In our case it was 1.6%, and the majority were due to puncture of the port by out-of-hospital personnel without adequate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the coracoid process of the scapula as a landmark for incision, thus minimizing incision variation [ 20 , 22 ]. In addition, vessel cutdown was the preferred method and the cephalic vein was the target vessel for port implantation because of its low complication rate [ 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of immediate complications with the percutaneous approach is near 0.05% [10,13,29]. In contrast, for the cut-down technique, the complication rate is nil [33,34,38]. Therefore, residents will have better success when they practice the cut-down technique.…”
Section: Discussionmentioning
confidence: 99%
“…US has also been used for investigating the status of the cephalic vein (their dimensions and deepness) [31,38]. This technique can be useful for the diagnosis of an anatomical absence of this vein.…”
Section: Discussionmentioning
confidence: 99%